PERLINDUNGAN LINGKUNGAN HIDUP MELALUI PEMBERIAN BANTUAN KREDIT OLEH PERBANKAN - Wadjedah Nursyamsi; Irwansyah Irwansyah; Nurfaidah Said (Faculty of Law, Universitas Riau, 2018)
This study aims to analyze protect the environment through the provision of credit assistance and supervision of credit granting by banks to protect the environment. This research is done by using empirical normative research method The results of this study indicate that: 1) Prevention of the bank in making credit agreements by including clauses prevention of environmental pollution must be done by the debtor. While repressively, the Bank is obliged to pay attention to the results of the PROPER assessment issued by the Ministry of Environment which is a mandatory requirement for the industry to apply for banking credit 2) OJK form of supervision on the provision of environmentally sound credit by the banks by ordering all LJK activities to establish sustainable financial system in which sustainable finance is defined as the overall support of the financial services sector to create sustainable economic growth by harmonizing economic, social and environmental interests.Keywords : Environment, Banking, Credit